The types of skippers described by Shu-Iti Murayama (Lepidoptera: Hesperiidae) - Chiba, Hideyuki; Tsukiyama, Hiroshi; Liang, Jia-Yuan; Wang, Shou-Ming; Shen, Zong-Yu; Hsu, Yu-Feng (Zootaxa, 2020)
Fifteen holotypes of Asian Hesperiidae taxa described by Shu-iti Murayama were examined, and their taxonomic status is discussed. We confirm that five are valid names while the rest are synonyms as indicated partially by previous authors. Valid species-level names are Aeromachus matudai (Murayama), Aeromachus bandaishanus Murayama & Shimonoya, Coladenia pinsbukana (Shimonoya & Murayama), and Sebastonyma suthepiana Murayama & Kimura. Valid subspecies-level name is Ochlodes yuchingkina Murayama & Shimonoya. In order to settle the taxonomic status of Pedesta masuriensis cuneomaculata Murayama, masuriensis and tali were studied morphologically and molecularly. As a result, we consider that masuriensis and tali are two different species and treat cuneomaculata as a junior subjective synonym of tali.